Cinematography Strategies in Promoting Local Culture: A Study of the Documentary ‘It’s More than Candlenut Indudur. - Sri Dwi Astuti Al Noor; Stefvany; Yosa Fiandra; Arief Budiman; Mohammad Firdaus Azman (Telkom University, 2025)
Nagari Indudur, located in IX Koto Sungai Lasi District, Solok Regency, West Sumatra, is a major producer of candlenut oil. With an annual contribution of Rp. 147,350,000, candlenut oil plays a crucial role in the local economy. However, limited accessibility and promotion remain major challenges for farmers.To support the introduction of candlenut oil products, the Indonesian Conservation Community (KKI) WARSI produced a short documentary titled